Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-020-80267-4
|View full text |Cite
|
Sign up to set email alerts
|

ROCK inhibition reduces morphological and functional damage to rod synapses after retinal injury

Abstract: Retinal detachment (RD) causes damage, including disjunction, of the rod photoreceptor-bipolar synapse, which disrupts vision and may contribute to the poor visual recovery observed after retinal reattachment surgery. We created a model of iatrogenic RD in adult female pigs to study damage to the rod-bipolar synapse after injury and the ability of a highly specific Rho-kinase (ROCK) inhibitor to preserve synaptic structure and function. This model mimics procedures used in humans when viral vectors or cells ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 81 publications
2
4
0
Order By: Relevance
“…This prospective study showed that the retinal damage induced by a RD is not restricted to the detached retina, but extends beyond the border to the attached retina in patients with fovea‐on retinal detachment. This supports the findings of previous animal studies by Halász, Lee and Francke who demonstrated that retinal damage is found not only in the detached retina but in lesser extent also in the attached retina (Francke et al, 2005; Halász et al, 2021; Lee et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This prospective study showed that the retinal damage induced by a RD is not restricted to the detached retina, but extends beyond the border to the attached retina in patients with fovea‐on retinal detachment. This supports the findings of previous animal studies by Halász, Lee and Francke who demonstrated that retinal damage is found not only in the detached retina but in lesser extent also in the attached retina (Francke et al, 2005; Halász et al, 2021; Lee et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, we hypothesize that the loss of retinal function in the attached retina is due to cellular damage mechanisms in the detached retina which spreads into the attached retina. Our hypothesis is supported by previous animal studies which have reported damage to the synapse between photoreceptor and bipolar cells in both attached and detached retina (Halász et al, 2021; Townes‐Anderson et al, 2017; Wang et al, 2016). This synaptic damage is due to rods retracting their presynaptic terminals and cones losing their synaptic invaginations (Halász et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the concentration of 1 µM of AR-13503, statistical significance was achieved when the proliferation rates were compared against untreated CECs (p < 0.05). A recent study reported a lower dose of AR-13503 to be effective at greater than 1000 times than Y-27632, and suggested the efficacy of this lower dosage to be highly specific for the effects against ROCK [66]; it is currently assessed as an implantable in subjects with neovascular age-related macular degeneration or diabetic macular edema (NCT03835884). Indeed, the results observed in the current study suggests that when used at a higher concentration of 10 µM, AR-13503 may be a suitable molecule for the purpose of corneal endothelial cell expansion protocols and cellular therapeutics, and it is currently the subject of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The following kinases were inhibited by more than 75% with 5 µM CompA: PKG1α, ROCK-I, p70S6K, and PKA (Supplementary Figure S1A). In addition to the roles in the aforementioned signaling pathways, these kinases have been implicated in retinal cell proliferation, function, and pathophysiology [24][25][26][27].…”
Section: Compounda Promotes In Vitro and In Vivo Rspc Proliferationmentioning
confidence: 99%